SIKAP DAN AKTIVITAS BIDAN DI DESA MEMBINA DUKUN BAYI DALAM MENOLONG PERSALINAN DAN MERAWAT BAYI - Mulyono N, Mulyono N; Sudibyo S, Sudibyo S; Qomariah, Qomariah; Riyasa, I Ketut; Riyanto M, Riyanto M (Lembaga Penelitian Universitas YARSI, 2005)
One of the main task and function midwife is to guide the health cadre and Traditional Birth Attendance (TBA). A Study of House Hold Health Survey (SKRT) in 1995 found that 48,4% childbirth is helped by TBA, 38,6% by midwife, 4,2% by doctor, 3,8% by nurse, and the rest by others or without help. Most of cases of tetanus neonatorum in Indramayu till 1998 occurred at the childbirth process helped by TBA. It was not known how midwives trained and supervised the TBA in helping childbirth and caring the babies. The desaign of the research was a cross-sectional one with the purpose to know the activities of midwives. Research locations were at several Puskesmas in Indramayu District. Result of the study were among others: midwives were not so busy in conduc-ting the main task, because most of them (70%) helped only one child birh of a mother per month and the number of BTA to be trained were only about 3 people. So they should have much time to coduct training more intensively to TBA. The training method used were most ?ceramah?and practical skill (59,6%). The language used was active native language. Whereas the majority of the training subjects (77%) were about caring navel string, understanding the complication of chilbirth (52%), and helping childbirth rightly (44%). The majority of equipment used for training were scissor (68%), and brush (58,4%).